Pre-existing arterial microcalcification and arteriovenous fistula failure - Nenad Petković; Radoslav Gajanin; Ljubica Djukanović (Биомедицинска истраживања, 2017)
Arterial microcalcification is common in patients with chronic kidney disease (CKD) and presents a significant predictor of both general and cardiovascularmortality. The study involved 22 patients (14 males, aged 60.5± 12.1) with chronic kidney disease (eGFR 11.9 ± 2.3 ml/min/1.73m2) undergoing their first AVF surgery. Radial artery specimens obtained from all patients during AVF creation were fixed and stained with hematoxylin and eosin for semiquantitative calcium quantification. Arterial microcalcification wasfound in ten (40.9%) patients. During 30 months after AVF surgery nine patients died, seven with a functioning AVF. Among these nine patients arterial microcalcification was found in five (p = 0.16). During the follow-up period unassisted AVF failure occurred in four (18.2%) patients, one of whom had arterial microcalcification (p=0.47).